KAJIAN TENTANG FOOD LOSS DAN FOOD WASTE: KONDISI, DAMPAK, DAN SOLUSINYA - Asri, Nyoman Puspa; Handoyono, Mitha Ayu (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2024)
The purpose of writing this article is an attempt to introduce readers to the problem of FoodLoss & Food Waste (FL&FW) in a comprehensive concept regarding conditions, impacts andsolutions for handling them. FL&FW has been a global issue for a long time, but until now itsimpact is getting more serious. The losses incurred by FL&FW are not only in the environmentalfield but are very complex including economic and social losses. Food and AgricultureOrganization/FAO has estimated that 1/3 of world food production or around 1.3 billion tonswhich is equivalent to 990 billion USD has been lost in vain. But on the other hand, about21,000 people die every day because of hunger. This topic will continue to be a central issue inthe coming years, because the amount of food that must be provided will also continue toincrease in line with the increasing world population and the problems caused by the Co-19pandemic. Reducing food waste is a priority scale to maintain sustainable food security. TheFL&FW issue since 2015 has been one of the programs of the Sustainable Development Goals(SDGs), on target 12.3 with a commitment to reduce food waste by half per capita by 2030.Therefore, all stakeholders (government, industry and society) must collaborate to implementingpolicies and cultural changes towards prevention of FL&FW on all fronts.